Interleaving Scheduling Algorithm for SLM Transactions in Mode S Surveillance Radar - Bria, Oscar N. (2018)
Mode S Secondary Surveillance Radar establishes selective and univocally addressed transactions with aircraft within its coverage while using efficiently the available budgets of time and energy. This benefits are key to supporting high-traffic density. A preliminary interleaving algorithm for the scheduling of Short Length Message transactions is presented and tested under a heavy load simulated scenario.